Research and Design of Hydrological Monitoring System Based on Beidou Short Message and LoRa - Zeng, Mingjin; Xia, Mengxi; Ren, Shuai; Ran, Yiqiang (2023 IEEE International Conference on Control, Electronics and Computer Technology (ICCECT), 2023)
Aiming at the current problems of hydrological monitoring in China, such as monitoring points located in remote areas, no communication network and poor real-time data collection, this paper proposes and designs a hydrological monitoring system based on Beidou short message and LoRa. The system consists of several collection terminals, data gateway, and monitoring terminal. The collection terminals send hydrological data to the data gateway by LoRa, the data gateway acquired multiple sets of hydrological data and reports them to the monitoring terminal through the Beidou short message module; the monitoring terminal also can send instructions to the collection terminals through the data gateway to realize the control of the collection terminals. By testing, the system meets the requirements of wide communication coverage, long-distance networking of collection terminals, low power consumption, and has wide application prospects.